Decoding tinnitus progression: neurochemical shifts in the anterior cingulate cortex revealed by magnetic resonance spectroscopy - Mengfang Gong; Shuting Han; Yongcong Shen; Yonggang Li; Ji-Sheng Liu; Duo-Duo Tao (Frontiers in Neuroscience)
BackgroundTinnitus persists as a significant public health challenge with elusive neurochemical underpinnings. Emerging evidence implicates dysregulated excitatory-inhibitory neurotransmission in the anterior cingulate cortex (ACC), a limbic-auditory hub governing tinnitus salience. This study investigates dynamic ACC neurochemical changes during tinnitus progression.MethodsUsing single-voxel magnetic resonance spectroscopy (MRS), GABA+/creatine (Cr) and Glx (glutamate+glutamine)/Cr ratios were measured in the ACC of 16 recent-onset (RO; <6 months), 22 chronic (CH; ≥6 months) tinnitus patients, and 26 healthy controls (HC). Tinnitus severity was assessed via tinnitometry and Tinnitus Functional Index (TFI).ResultsRO patients exhibited significantly reduced ACC GABA+/Cr compared to CH and HC groups (p < 0.05), while CH and HC showed no differences. GABA+/Cr positively correlated with tinnitus duration across patients (r = 0.364, p = 0.025). Although Glx/Cr did not differ between groups, elevated Glx/Cr associated with higher tinnitus pitch-matching frequencies (r = 0.421, p = 0.008) and emotional distress (TFI-E; r = 0.370, p = 0.022), though these findings did not survive multiple comparison correction.ConclusionEarly tinnitus is characterized by ACC GABAergic deficits, while chronicity features normalized GABA+/Cr levels—suggesting compensatory neuroplastic restoration of inhibition over time. Glutamatergic activity may modulate perceptual and emotional dimensions of tinnitus. These phase-specific ACC neurochemical shifts highlight potential therapeutic targets for arresting tinnitus progression. Longitudinal studies are warranted to validate temporal dynamics.